Impact of black cumin and green tea on fertility, immunity and offspring morphology during reproductive aging in mice (Bangladesh Journal of Animal Science, 2023)
With the advancement of age in mammalian females, the reproductive ability is severely compromised, and infertility occurs. Black cumin seeds and green tea are believed to have pro-oxidant effects against various age-related disorders. Using mice model, this study was conducted to elucidate the impact of black cumin and green tea on fertility and offspring morphology of mammalian females during reproductive aging. For this, twenty aged female mice (£180 days old) were served either with or without black cumin through feed, green tea through drinking water, or their combination. The mice were regularly checked for estrus cycle and mated with males. Similar reproductive patterns were observed in all the groups up to 285 days. After that, weak estrus or anestrus was observed in the control group; however, the active reproductive period was observed to extend up to 350, 375, and 432 days in mice treated with black cumin, green tea, and their combination, respectively. Accordingly, the treatment of black cumin and green tea significantly increased the average number of pups per litter, having comparatively higher birth weight and weaning weight. Moreover, the duration of hair development and eye-opening were significantly reduced in all treated mother. The serum immunoglobulin results revealed higher immunity in mice treated with black cumin and green tea treatment either separately or in combination. Similarly, healthy ovarian follicles with a compact layer of granulosa cells and expanded cumulus cell layer surrounded by oocytes in all the treated mice compared to those of untreated mice. These findings will be helpful for developing breeding strategies during the reproductive aging of mammalian females.Bangladesh Journal of Animal Science 52 (1): 29-37, March 2023